1998
DOI: 10.1108/10662249810231041
|View full text |Cite
|
Sign up to set email alerts
|

Facing life without the Internet

Abstract: The size of that section of the electronic market place known as the Internet is substantially dependent on how many people acquire and retain Internet access. This core of Internet users is the bedrock on which electronic commerce will be built. More attention has been given to the reasons why people join the Internet community than to their motivation for leaving. We therefore sought to carry out exploratory research into the thinking of some of the likely Internet defectors in order to identify intelligent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…This, in turn, may lead to ignorance or high selectivity of information (Herbig and Kramer, 2001). Indeed, there is growing evidence of a large body of ex-internet users who have decided to forego cyberspace (Kingsley and Anderson, 1998) as well as to resist online interaction (Andrews et al, 2002). Nevertheless, as for example, Freeman (in Thorne et al, 2003: 74) suggests, '.…”
Section: Computer Ethics and Ethical Consumerismmentioning
confidence: 92%
“…This, in turn, may lead to ignorance or high selectivity of information (Herbig and Kramer, 2001). Indeed, there is growing evidence of a large body of ex-internet users who have decided to forego cyberspace (Kingsley and Anderson, 1998) as well as to resist online interaction (Andrews et al, 2002). Nevertheless, as for example, Freeman (in Thorne et al, 2003: 74) suggests, '.…”
Section: Computer Ethics and Ethical Consumerismmentioning
confidence: 92%
“…According to the literature, the digital divide is caused by social factors such as age, gender, education, status, income and local infrastructure (Clayton & Macdonald, 2013;Hindman, 2000;Kingsley & Anderson, 1998). Therefore, not only the different types of individuals, but also the different groups could be digitally isolated without necessarily belonging to groups traditionally excluded, at least not from a social conception of exclusion; in fact, there may actually be digitally excluded people of all kinds, for any of the reasons listed above.…”
Section: Physical and Virtual Barriersmentioning
confidence: 99%
“…Internet addiction Previous research has alleged that excessive internet use can be pathological and addictive, which is treated as internet addiction disorder (IAD) in clinical settings (Furnell and Warren, 1997;Kingsley and Anderson, 1998;Mafé and Blas, 2006;Widyanto and Griffiths, 2006). Past studies on internet addiction revealed numerous symptoms shared by other forms of addiction, including substance-based addictions, such as tolerance, withdrawal, preoccupation, numerous unsuccessful attempts to cut down use of the internet, and feeling restless without internet Widyanto and Griffiths, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%